(k, n) secret image sharing scheme with privileged set. (March 2023) - Yang, Ching-Nung; Li, Peng; Kuo, Hsin-Chuan
Abstract: In traditional ( k, n ) threshold secret image sharing (SIS) scheme, all participants play the same roles in the revealing process. The threshold value k is reflected by the security level, which is a fixed integer predetermined before sharing. However, in practice of SIS, some participants are more important than others. These important participants have the privilege that they can reveal the secret image with smaller threshold value. In this paper, we propose the first ( k, n )-SIS with privileged set (SISPS) scheme. There is a privileged set of participants. Normally, the secret image can be revealed by any k out of n participants. Besides, it also can be revealed by kp privileged participants, where kp < k . The privileged set can be used as hidden set, authentication set in different applications. We also further discuss the applications of SISPS used in progressive mode and two SISPS with the same privileged set. Some experiments are conducted to show the effectiveness of the proposed SISPS.